General aspects of drug interactions with systemic antifungals in a retrospective study sample Aspectos gerais de interações medicamentosas com antifúngicos sistêmicos em um estudo amostral retrospectivo - Juliano Vilaverde Schmitt; Giovana Bombonatto; Stella Maris Trierweiler; Andrea Buosi Fabri (Anais Brasileiros de Dermatologia, 2013)
A retrospective study evaluating hepatic laboratory alterations and potential drug interactions in patients treated for onychomycosis. We evaluated 202 patients, 82% female. In 273 liver enzyme tests, there were changes in only 6%. Potential drug interactions were identified in 28% of patients for imidazole and 14% for terbinafine. The risk of potential interactions increased with the patient's age and use of multiple drugs. Estudo retrospectivo avaliando alterações laboratoriais hepáticas e potenciais interações medicamentosas em pacientes tratados para onicomicose. Foram avaliados 202 pacientes, sendo 82% do sexo feminino. Em 273 exames de enzimas hepáticas, houve alterações em apenas 6%. Potenciais interações medicamentosas foram identificadas em 28% dos pacientes para imidazólicos e 14% para terbinafina. O risco de interações potenciais aumentou com a idade do paciente e o uso de múltiplas medicações.